Integrating Sustainable Development Goals in Higher Education: A Qualitative Case Study on Institutional Practices and Transformative Learning - Abdelbasit Gadour (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2012)
This study explores how higher education institutions integrate SDGs into their academic and institutional practices using a qualitative case study approach. Data were collected through semi-structured interviews with educators, students, and administrators, complemented by document analysis of institutional sustainability policies and academic programs. The findings reveal that although many universities demonstrate formal commitments to sustainability through strategic plans and policy frameworks, practical implementation remains limited due to several challenges, including insufficient faculty training, institutional resistance to interdisciplinary collaboration, and limited resources. The study concludes that effective SDG integration requires stronger institutional support, interdisciplinary collaboration, and the adoption of human-centered educational models. By fostering transformative learning environments, universities can play a more active role in empowering students as agents of sustainable development.